In vitro evaluation of coils for endovascular therapy. - Marks, M P; Tsai, C; Chee, H (American Journal of Neuroradiology, 1996)
PURPOSE To evaluate the physical characteristics and behavior of coils for endovascular therapy.METHODS Mechanically detachable coils were constructed with simple helical (4 mm X 10 cm and 8 mm X 30 cm) and pretzel shapes (4 mm X 5 cm) made from three metals using 0.003- and 0.004-in wire. Stiffness or pliability, frictional resistance, shape memory, and coil stability were evaluated in vitro.RESULTS The 0.004-in wire stock coils proved significantly stiffer when compared with the 0.003-in coils. Tungsten coils proved least pliable; platinum coils were intermediate in stiffness; and nitinol coils were softest. Frictional resistance in the catheter was greatest for stiffer coils. The 5-cm pretzel coil consistently created more frictional force than the 10- or 30-cm simple helical coils. Despite a shorter length, the 4-mm simple helical coil exerted more frictional force than the 8-mm coil. Stiffer metal coils constructed of larger-diameter wire (0.004 in) were more stable than softer coils.CONCLUSION Stiffer coils exert greater frictional forces within the catheter and a greater resistive force during bending but are more stable after placement. Frictional forces also depend on the complex three-dimensional shape of the coil and the diameter of the turns in that shape rather than coil length. These data suggest that a family of coils of different metals is optimal for varied intravascular needs.